Alérgenos y su incidencia en el desencadenamiento de rinitis alérgica en niños de 1 a 5 años, ciudadela Otto Arosemena, Babahoyo, Los Rios, periodo septiembre 2017 - febrero 2018 - Valverde Haz, Lisseth Andrea (2018)
Allergic rhinitis is a very common problem throughout the world, affecting at least 10 to 30% of the population, and its prevalence is increasing. Allergic rhinitis is an inflammation of the nasal mucosa, which occurs as a result of a systemic inflammatory reaction mediated by immunoglobulin E (IgE) and induced by exposure to an allergen. The objective was to determine the incidence of allergens in the triggering of cases of allergic rhinitis in children from 1 to 5 years of the Otto Arosemena citadel, Babahoyo Los Ríos, September 2017 to February 2018, in a population of 72 children from 1 to 5 years of age, in a non-experimental investigation of descriptive-explanatory type, and as a result of the research we have that allergens are incidents in allergic bronchitis in children, this caused by the little interest of the mothers to control the disease because they do not identify the causing allergens or the signs and symptoms of the disease; as a major allergen are smokers, household cleaning, mixed constructions of houses, requiring a prevention education program to allergic bronchitis in order to counteract its effects and benefit children for better development and quality of life.